Electrically tunable lateral spin-valve transistor based on bilayer CrI3 - Damiano Marian; David Soriano; Emmanuele Cannavó; Enrique G. Marin; Gianluca Fiori (npj 2D Materials and Applications, 2023)
Abstract The recent discovery of two-dimensional (2D) magnetic materials has opened new frontiers for the design of nanoscale spintronic devices. Among 2D nano-magnets, bilayer CrI3 outstands for its antiferromagnetic interlayer coupling and its electrically-mediated magnetic state control. Here, leveraging on CrI3 magnetic and electrical properties, we propose a lateral spin-valve transistor based on bilayer CrI3, where the spin transport is fully controlled via an external electric field. The proposed proof-of-concept device, working in the ballistic regime, is able to both filter (>99%) and select ON/OFF the spin current up to a ratio of ≈102, using a double split-gate architecture. Our results obtained exploiting a multiscale approach ranging from first-principles to out-of-equilibrium transport calculations, open unexplored paths towards the exploitation of bilayer CrI3 or related 2D nano-magnets, as a promising platform for future electrically tunable, compact, and scalable spintronic devices.